Migration practice as creative practice : an interdisciplinary exploration of migration - Hack-Polay, Dieu Donné; Mahmoud, Ali B.; Rydzik, Agnieszka; Rahman, Mahfuzur; Igwe, Paul Agu; Bosworth, Gary (Emerald Publishing Limited, 2021)
Migration Practice as Creative Practice: An Interdisciplinary Exploration of Migration presents an in-depth evaluation of migrants' contributions to modern socio-economic structures. Leading with a discussion of the historical construction of migration and what it signifies in the modern globalised economies, an interdisciplinary range of contributors examine the interaction of migrants with new cultures, migrants' embeddedness into new environments and what that signifies for community relations. The book discusses the creative energies that migrants bring to the private and public spheres. Migration Practice as Creative Practice examines how migrants use their social lives, lived experiences, the process of identity formation and histories to inject positive 'newness' into host cultural and economic architectures. The book calls for more creative ways of researching migrant lived experiences and brings to life the different ways of approaching migrant research for scholars today.
Includes index.
Keywords: Immigrants -- Social conditions.; Cultural awareness.; Emigration and immigration -- Social aspects.; Immigrants -- Economic conditions.; Social Science, Emigration & Immigration.; Population & demography.; elektronické knihy; electronic books